Phase II clinical trial of pembrolizumab efficacy and safety in advanced adrenocortical carcinoma. Issue 1 (18th September 2019) - Habra, Mouhammed Amir; Stephen, Bettzy; Campbell, Matthew; Hess, Kenneth; Tapia, Coya; Xu, Mingxuan; Rodon Ahnert, Jordi; Jimenez, Camilo; Lee, Jeffrey E.; Perrier, Nancy D.; Boraddus, Russell R.; Pant, Shubham; et al.
Abstract : Background: Adrenocortical carcinoma (ACC) is a rare malignancy without good treatment options. There are limited data about the use of immunotherapy in ACC. We investigated the efficacy and safety of pembrolizumab in patients with metastatic ACC. Methods: This is a pre-specified cohort of a single-center, investigator-initiated, phase II clinical trial using pembrolizumab monotherapy in patients with rare malignancies. Patients must have had prior treatment fail in the past 6 months before study enrollment. Patients were enrolled from August 2016 to October 2018. Follow-up data were updated as of March 26, 2019. Patients received 200 mg pembrolizumab intravenously every 3 weeks without concomitant oncologic therapy. The primary endpoint was non-progression rate (NPR) at 27 weeks. Other endpoints included adverse events, tumor responses measured independently by objective radiologic criteria, and select immunological markers. Results: Sixteen patients with ACC (including eight women [50%]) were included in this cohort. Ten patients (63%) had evidence of hormonal overproduction (seven had cortisol-producing ACC). Non-progression rate at 27 weeks was evaluable in 14 patients, one patient was lost to follow-up, and one patient left the study because of an adverse event. Five of 14 patients were alive and progression-free at 27 weeks (non-progression rate at 27 weeks was 36, 95% confidence interval 13–65%). Of the 14 patients evaluable for imaging response by immune-related Response Evaluation Criteria in Solid Tumors, two had a partial response (including one with cortisol-producing ACC), seven had stable disease (including three with cortisol-producing ACC), and five had progressive disease, representing an objective response rate of 14% (95% confidence interval 2–43%). Of those who had stable disease, six had disease stabilization that lasted ≥4 months. Severe treatment-related adverse events (≥grade 3) were seen in 2 of 16 patients (13%) and resulted in one patient discontinuing study participation. All studied tumor specimens (14/14) were negative for programmed cell death ligand-1 expression. Thirteen of 14 tumor specimens (93%) were microsatellite-stable. Eight of 14 patients (57%) had a high tumor-infiltrating lymphocyte score on immunohistochemistry staining. Conclusions: Single-agent pembrolizumab has modest efficacy as a salvage therapy in ACC regardless of the tumor's hormonal function, microsatellite instability status, or programmed cell death ligand-1 status. Treatment was well tolerated in most study participants, with a low rate of severe adverse events. Trial registration: ClinicalTrials.gov identifier: NCT02721732, Registered March 29, 2016.